COMPARATIVE CHARACTERISTICS OF REFRACTORY COMPOUNDS SYNTHESIS METHODS - Malyshev, Victor; Gab, Angelina; Shakhnin, Dmytro; Nesterenko, Tetiana; Rumyantsev, Volodyslav; Lichkonenko, Nataliya (Scientific Journal "Metallurgy", 2022)
Based on the analysis of classifications of methods for synthesis of refractory com-pounds given in the literature and compliance with the principles of adequacy of starting components and type of chemical reactions (kinetic mechanism – a certain number and sequence of reaction stages), classification of methods for synthesis of these compounds is proposed. It includes six methods: direct synthesis of elements; synthesis from solutions in melts; metallothermic reduction of metal oxides; reduction of oxides and other compounds by non-metals and their compounds; gas phase synthesis; electrolysis of melts and solutions in melts (high-temperature electrochemical synthesis). The essence, advantages and disadvantages of each method are singled out. Each synthesis method is reflected in the main indicators of technologies and characteristics of synthesized compounds: the presence of inexpensive and affordable components, simplicity of equipment and technologies, control of the synthesis process, large scale, process continuity, finished products, single crystals, accurate compound composition, purity, high yield and simplicity product department, application in industry. The main indicators of the existing methods of realization of synthesis methods are given, namely: initial components, synthesis temperature, atmosphere in the cell, process duration. The main advantages of direct synthesis from elements are the possibility of obtaining large quantities of refractory compounds and the short duration of the process, and the disadvantage is the difficulty in obtaining the exact composition of the compound. The main advantages of synthesis from solutions in melts are the simplicity of the synthesis process and the possibility of obtaining compounds of a certain contribution, and the disadvantages – low product yield and cost of expensive solvents.